2017
DOI: 10.1002/pd.5019
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Duchenne muscular dystrophy in 131 Chinese families with dystrophinopathy

Abstract: Accurate genetic diagnosis of the proband is important for preventing recurrence in at-risk families. The present results demonstrate the importance of considering maternal germline mosaicism in the genetic assessment. Prenatal diagnosis should be suggested to the parent with a DMD proband whether carrier testing found the causative mutation in the mother's blood or not. Finally, we have developed a prenatal diagnosis algorithm for dystrophinopathies that combines multiplex ligation-dependent probe amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…In our cohort, mutation of DMD gene was identified in 1 case (Case 17). Mutations of DMD gene locus may cause Duchenne muscular dystrophy (DMD), Becker muscular dystrophy, or cardiomyopathy . The pregnancy was terminated at last.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, mutation of DMD gene was identified in 1 case (Case 17). Mutations of DMD gene locus may cause Duchenne muscular dystrophy (DMD), Becker muscular dystrophy, or cardiomyopathy . The pregnancy was terminated at last.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical genetic counseling, prenatal diagnosis is recommended for pregnant female carriers with a family history of DMD to prevent recurrence in at-risk families. Some researchers even believed that prenatal diagnosis was also suggested for the proband's mother without the causative mutation in their blood considering maternal germline mosaicism (Wang et al, 2017). In this study, the mother (I-2) had raised a DMD-affected boy, so we carried out targeted DMD gene testing and Sanger sequencing in present family for prenatal diagnosis, which identified that the fetus (II-2) also carried the widely reported pathogenic mutation (c.9100C>T, p.Arg3034Ter) (Dent et al, 2005;Flanigan et al, 2009;Magri et al, 2011) in a heterozygous state.…”
Section: Discussionmentioning
confidence: 99%
“…The term 46,XX testicular disorders of sex development (46,XX testicular DSD), previously termed as male sex reversal, was introduced by the "Chicago Consensus" in 2006, for individuals who manifest inconsistency of chromosomal, gonadal, or anatomical sex with a male phenotype and a female karyotype (Hughes et al, 2006) and was firstly described by de la Chapelle et al in 1964(De la Chapelle et al, 1964. The occurrence rate of 46,XX testicular DSD ranges from 1/20,000 to 1/100,000 (de la Chapelle, 1981;SS, 1994;Berglund et al, 2017;Wang et al, 2017), with considerable geographic variations. Approximately 80% of individuals affected by 46,XX testicular DSD show typical male phenotype at birth, and present with infertility or delayed puberty.…”
Section: Introductionmentioning
confidence: 99%
“…8 Currently, for the prenatal diagnosis of DMD, a variety of sampling methods including villi tissue, amniotic fluid, umbilical cord blood and a variety of molecular detection methods including MPLA, real-time PCR, DHPLC, and DNA sequencing have been adopted. [18][19][20] Gonorazky et al reported that RNA analysis would be a critical required element for establishing pathogenicity of noncoding mutations for a significant fraction of the currently "unsolved" cohort of patients with DMD. 21 DMD transcript mutations can unable to identify though chorionic villus or amniocentesis techniques.…”
Section: Discussionmentioning
confidence: 99%